The Acquisition of Tense and Aspect By Francophone Learners of English - Balcom, Patricia (Papers from the Annual Meetings of the Atlantic Provinces Linguistic Association (PAMAPLA) / ACTES DES COLLOQUES ANNUELS DE L’ASSOCIATION DE LINGUISTIQUE DES PROVINCES ATLANTIQUES (ACAALPA)., 2002)
There have been several proposals to account for the L2 acquisition of tense and agreement: one is that the category is transferred from the L1 but its features are underspecified and learners need to acquire the L2 value; another is that the category and the value of its features are transferred from the L1 and the L2 value may be acquired when learners, internalized grammars do not match the input. Some researchers contend that L2 features are never acquired so that learners' final state diverges from that of native speakers. In this paper I explore the L2 acquisition of tense and agreement in a study which involved 42 francophone learners of English, 14 each at the beginning, intermediate and advanced levels. The task was a narrative with 44 blanks to be filled in with an appropriate form of the verb. The results show that there is a strong correlation between level and performance on the task, and that advanced learners exhibited native-like performance. Moreover there was transfer of semantic features of tense and aspect from L1 French to L2 English.